ANALYSIS OF EFFECTIVENESS AND CONTRIBUTION OF REGIONAL TAX REVENUE BEFORE AND AFTER THE IMPLEMENTATION OF THE TAPPING BOX TO OPTIMIZE REGIONAL ORIGINAL INCOME IN POLEWALI MANDAR - Yusriana Sri Ana; Basri Modding; Mursalim Mursalim (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
The title of the research is Analysis of the Effectiveness and Contribution of Regional Tax Revenue Before and After the Application of the Tapping, Box System to Optimize the Regional Original Income (PAD) of Polewali Mandar City. This study aims to learn more about optimizing the use of the Tapping Box tool in PAD collection. Tapping Box is a tool owned by the local government and its use is left to the business owner who is subject to tax. This study uses a quantitative descriptive method that uses secondary data. The sample uses data on the realization of regional income, targets, and PAD for Polewali Mandar Regency in 2018-2019. The data analysis technique uses the formulation of the effectiveness and contribution of the 2012 Halim regional tax. The results of this study indicate that the effectiveness in the 2018-2020 every year increases by an average of 133%, so the tool is effective in tax revenue. Contributions in 2018-2019 with an average of 44.41% are very less because PAD does not only affect Hotel taxes, Restaurant taxes, and Entertainment Taxes, there are separated income and other legitimate PAD.